FRASE “BENCANA KARENA MUSLIHAT DAN KHIANAT” SEBAGAI PENANDA UTAMA PADA DRAMA HAMLET, PRINCE OF DENMARK KARYA WILLIAM SHAKESPEARE (SEBUAH KAJIAN SEMIOTIK) - Anggarani Wilujeng (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2011)
The objective of this writing is to reveal and show the phrase of “lest more mischief, including plots and errors” as a primary signifier in the drama of William Shakespeare’s Hamlet, Prince of Denmark using semiotics approach. By using semiotics approach, in the text, the writer can find a primary signifier of the phrase of “lest more mischief, including plots and errors” through the signs and type; the index, resulting in the overall meaning of the text.